Factors of Speaking Anxiety on Students' Speaking Ability: A Systematic Literature Review - Soma, Robi; Tanjung, Raja Mahendra (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2026)
The purpose of this research was to examine what factors of speaking anxiety causing the EFL students to become incapable to express their ability in using English as a foreign language. The four current articles reviewed were taken from Google Scholar and Semantic Scholars databases limited to those which were published three years namely in the year of 2024 to 2026 to see the most recent development regarding factors of speaking anxiety. The researchers applied Systematic Literature Review as the method of research. The result of the review indicated that there were five main factors of anxiety obtained in the articles reviewed by the researchers such as: lack of/low self-confidence, fear of making mistakes in speaking, the limited number of vocabulary the students had, fear of negative evaluation especially by their peers and the last one was the inaccurate use of grammar. Some suggestions and recommendations to overcome foreign language anxiety problems were given at the last part of the article as well as implications and limitations.